Examinations without Patients: Postgraduate Exit Exams in Psychiatry during COVID-19 Pandemic - Thanapal Sivakumar; Shyamsundar Arumugham; Prabhat Kumar Chand; Pratima Murthy; Mathew Varghese (Journal of Psychiatry Spectrum, 2022)
The coronavirus disease 2019 pandemic posed unique challenges in conducting postgraduate exit exams in psychiatry. Many patients could not travel to the hospital due to lockdown. Patient and student safety were essential considerations. Getting external examiners was a challenge. Instead of actual patients, the exam pattern was modified to utilize case vignettes, case histories, and trained volunteers. The novelty of the experience and shortcomings of conducting postgraduate exit exams without a patient at a tertiary care center is described in this article.